THE RELATIONSHIP BETWEEN WORK MOTIVATION AND ACADEMIC SUPERVISION WITH THE TEACHERS' PERFORMANCE AT PANGKATAN VOCATIONAL SCHOOL 1. - R. Beresman Sianturi; Effendi Napitupulu; Saut Purba (JURNAL PROINTEGRITA, 2019)
The purpose of this study was to find out whether there was a relationship between work motivation and academic supervision with the performance of the teachers of State 1 Vocational School. The technique of sampling in this study was total sampling with 48 respondents. Data collection techniques using questionnaires, before the questionnaire was distributed first carried out trial analysis, namely test validity and reliability. Hypothesis testing is done by using a correlation test. Based on the results of the correlation test that the value of r12y> 0 and the value of sig 000 <0.05, it means that the relationship between work motivation and academic supervision with the performance of teachers at SMK Negeri 1 Pangkatan is significant. Suggestions from this study are (1) In order for teachers in State Vocational School 1 Departure to increase work motivation by supporting one another, (2) So that teachers in 1 Departure Vocational School always make school work planning, (3) For teachers in Vocational Schools Negeri 1 Pangkatan creates a conducive school environment for learning, (3) So that teachers at SMK Negeri 1 Pangkatan carry out work in a fun way.